1994
DOI: 10.1016/s0006-3495(94)80747-7
|View full text |Cite
|
Sign up to set email alerts
|

Power spectra and cooperativity of a calcium-regulated cation channel

Abstract: In this article we show that a channel complex of cooperatively interacting subunits can produce a power law spectrum with the slope of the spectrum depending on the strength of the cooperative interaction. The effects of cooperativity are explored via a computational model of a calcium-regulated cation channel for which new data is presented. The results, which concern "flickering" conductances, are correlated with prior work on critical fluctuations in the Ising model of ferromagnetism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…It has been observed that the Fourier transform of ionic current through BK channels is not a Lorentzian curve as would be expected for statistically independent channels but exhibits a power law with an exponent between -1 and -2 [47]. The 1/f flicker noise can be caused due to various reasons; co-operativity between channels [48], second-order conformation change in the channel leading to incomplete closure of the pore or obstruction of ion passage across the channel [49,50]. Whether these observations apply to other classes of voltage-gated ion channels remains unclear [51].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the Fourier transform of ionic current through BK channels is not a Lorentzian curve as would be expected for statistically independent channels but exhibits a power law with an exponent between -1 and -2 [47]. The 1/f flicker noise can be caused due to various reasons; co-operativity between channels [48], second-order conformation change in the channel leading to incomplete closure of the pore or obstruction of ion passage across the channel [49,50]. Whether these observations apply to other classes of voltage-gated ion channels remains unclear [51].…”
Section: Discussionmentioning
confidence: 99%
“…Possible candidates include ionic channels, in which fractal patterns of channel gating in single-channel recordings were observed and mathematical models of channel gating accounting for this property were formulated. 26,27 Moreover, electrophysiological studies showed the presence of fractal characteristics in the oscillations of the membrane potential. 28 Also, it was shown that, while isolated cardiac cells beat stochastically, fractal patterns of activity establish when a large number of cells are electrically coupled and synchronize.…”
Section: Intrinsic Power-law Behavior: Possible Mechanismsmentioning
confidence: 99%
“…Calcium has been implicated in the neurochemistry of synaptic signal transduction and memory formation for some time (10, 6063). This may turn out to helpful when one attempts to link mental processes to actual molecular processing.…”
Section: From Recurrent Network To Molecular Substrates Of Consciousmentioning
confidence: 99%
“…In an Ising model, collective behavior of interacting parts such as magnetic particles (spin up or down) or neurons (on or off) is based on simple neighboring rules (ferromagnetic/activating, anti-ferromagnetic/inhibiting, or non-interacting). Curiously, the Ising model is applicable to the opening state of ion channels (60, 6970), which implies that the fractal neural network activity can be mapped onto the collective opening of ion channels in the dendritic tree. Therefore, fractality is preserved when the pattern of activity nodes in dendritic trees is mapped onto the opening/closing distribution of ion channels in a hexagonal lattice (Figs.…”
Section: From Recurrent Network To Molecular Substrates Of Consciousmentioning
confidence: 99%